LRRK2 is a negative regulator of Mycobacterium tuberculosis phagosome maturation in macrophages. (22nd May 2018) - Härtlova, Anetta; Herbst, Susanne; Peltier, Julien; Rodgers, Angela; Bilkei‐Gorzo, Orsolya; Fearns, Antony; Dill, Brian D; Lee, Heyne; Flynn, Rowan; Cowley, Sally A; Davies, Paul; Lewis, Patrick A; et al.
Abstract: Mutations in the leucine‐rich repeat kinase 2 (LRRK2) are associated with Parkinson's disease, chronic inflammation and mycobacterial infections. Although there is evidence supporting the idea that LRRK2 has an immune function, the cellular function of this kinase is still largely unknown. By using genetic, pharmacological and proteomics approaches, we show that LRRK2 kinase activity negatively regulates phagosome maturation via the recruitment of the Class III phosphatidylinositol‐3 kinase complex and Rubicon to the phagosome in macrophages. Moreover, inhibition of LRRK2 kinase activity in mouse and human macrophages enhanced Mycobacterium tuberculosis phagosome maturation and mycobacterial control independently of autophagy. In vivo, LRRK2 deficiency in mice resulted in a significant decrease in M. tuberculosis burdens early during the infection. Collectively, our findings provide a molecular mechanism explaining genetic evidence linking LRRK2 to mycobacterial diseases and establish an LRRK2‐dependent cellular pathway that controls M. tuberculosis replication by regulating phagosome maturation. Synopsis: Possible immune functions of LRRK2, a kinase frequently mutated in Parkinson's disease, have remained ill‐defined. Genetic, pharmacological and proteomics approaches now reveal it as a negative regulator of phagosome maturation in macrophages, thereby affecting the control of Mycobacterium tuberculosis (Mtb) infection. LRRK2 loss targets Mtb to phagolysosomes and limits Mtb replication. LRRK2 inhibition enhances phagosome maturation in macrophages. LRRK2 activity is required for the recruitment of class III PI3K/Rubicon into phagosomes. Loss of LRRK2 enhances innate immunity to Mtb in mice. LRRK2 KO alters inflammatory profiles after Mtb infection in vitro and in vivo . Abstract : The Parkinson's disease‐associated kinase LRRK2 affects innate immune control of mycobacterial infections in vitro and in vivo via phagosome recruitment of class III PI3K and Rubicon.